One : stories of one-room flats in Block 2, Jalan Kukoh. - Lim, Rong Shan. (2009)
In the 1960s to 1970s, 1 and 2-room flats were built to move Singaporeans out of slums and kampongs and into properly planned urban development. With Singapore’s rapid economic development, the function of rental flats has evolved to become an affordable housing solution for needy Singaporeans. Since the 1970s, demand for rental housing dropped as Singaporeans moved into bigger and better housing. However, from 2005, there has been a surge of demand for rental housing. This upswing in demand is generated by an increasing number of young families as well as middle-class Singaporeans who downgraded to rental housing. Using the concept of reporting on stories from a single block of 1-room flats, this illustrated feature aims to unravel the issues and challenges faced by rental housing residents, both new and old, in dealing with their living environment. This feature also aims to raise a discussion on the increasing trend of young families moving into rental housing.